tm - Technisches Messen : Plattform für Methoden, Systeme und Anwendungen der Messtechnik (Oldenbourg Wissenschaftsverlag, 1931)
TM - Technical Measurement is a professional journal for application-based industrial measurement technology, a key component of systems for automation, process monitoring, quality control, and security. It's the official organ of the AMA (Association for Sensor Technology) and the NAMUR (Process-Industry Interest Group for Automation Technology). It also includes notifications from the GMA (VDI/VDE-Society for Measurement and Automatic Control).